Strengthening the Marketing Strategies for the Traditional Property Developer in Malaysia (Global Business Management Review (GBMR), 2019)
During the global economic downturn not only affecting Malaysian property industry but it was also impacted the global property industry, during the economic recession was increasing market competitive eventually the Malaysia property industry is even more challenging with oversupplying properties as more and more building been completed in the markets, but the sales are slow during the economic downturn. Therefore, an effective marketing plan is an integral aspect even for all types of businesses, which also been widely recognized and acknowledged, as an effective marketing plan has a significant positive impact on all kinds of businesses. The goal of this case study is to strengthen the marketing strategies with access and examine the marketing strategies for the traditional property developer firm in Malaysia with the targeted company name is 'S,' a direct interview with the marketing team was applied to examine the company marketing strategy. Strengthening of the marketing strategies plans with considering the marketing factors such as marketing positioning, marketing recognition, diverse customer base, marketing strategies effectiveness, internal environment, promotion strategies, promotion budgets, and product design and technology. The finding of this case study is providing a solution for strengthening the marketing strategies for the traditional property developer firms even during the economic downturn which able to strengthen and improve the company market share and reduce the burden with selling off the completed balance unsold stock units, as this traditional property developer firm need to upgrade, update and improve their marketing strategies.